Redescriptions of Pugettia quadridens (De Haan, 1837) and P. intermedia Sakai, 1938 (Crustacea: Brachyura: Epialtidae) with description of a new species - Ohtsuchi, Naoya; Kawamura, Tomohiko (Zootaxa, 2019)
Pugettia quadridens (De Haan, 1837) and its closely similar congener, P. intermedia Sakai, 1938, are redescribed and illustrated and their possible infraspecific variations related to sexual, ontogenetic, and environmental differences are discussed. As a result, a new species, Pugettia ferox, which had long been believed to be a local variant of P. quadridens sensu lato in the northeast Japan, is described. Despite moderate sexual dimorphism and considerable variability related to their ontogeny, the three species can be distinguished from each other by the combination of various morphological characters including the structure of the orbital region and male first gonopods. The patterns of ontogenetic morphological and morphometric changes in the chelipeds, gonopods, and pleons are also differentiated among the three species. The updated distribution ranges of three species greatly overlap in the northeast Asian waters, although P. quadridens sensu stricto is distributed more southward than P. ferox n. sp.. Distinguishing characters between P. quadridens s.s. and P. pellucens Rathbun, 1932, and between P. intermedia and P. vulgaris Ohtsuchi, Kawamura & Takeda, 2014, are revised.